Intensive Care 2017
DOI: 10.5772/intechopen.68591
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Monitoring in the Intensive Care Unit

Abstract: Monitoring is a cognitive aid that allows clinicians to detect the nature and extent of pathology and helps assessment of response to therapy. The cardiovascular system is the most commonly monitored organ system in the critical care setting. It helps identify the presence and nature of shock and guides response to resuscitation by detection of cardiac rate and rhythm, evaluation of volume state, cardiac contractility and systemic vascular resistance. Newer technologies allow greater assessment of oxygen deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…From a clinical perspective, the model can be extended to the prioritization of patients who are candidates for admission to the intensive care unit, thus facilitating the identification of patients who would benefit from early admission to the ICU [41]. It would also facilitate the management of patients admitted to the ICU to improve hemodynamic management [42,43], anticipate the complications associated with mechanical ventilation [44], and anticipate intubation [45].…”
Section: Discussionmentioning
confidence: 99%
“…From a clinical perspective, the model can be extended to the prioritization of patients who are candidates for admission to the intensive care unit, thus facilitating the identification of patients who would benefit from early admission to the ICU [41]. It would also facilitate the management of patients admitted to the ICU to improve hemodynamic management [42,43], anticipate the complications associated with mechanical ventilation [44], and anticipate intubation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Haemodynamic and respiratory indicators such as blood pressure, pulse rate, respiratory rate, in the ICU are essential for preventing organ failure by ensuring stability between oxygen delivery and demand in the relevant tissues (Majumdar, 2017). Ultimately, when the ICU patient was with family, oxygen saturation improved, and the patient's oxygen demand decreased and PFCC is considered an important treatment guideline for ICUs to help patients and their families navigate the abovementioned challenges (Khaleghparast et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Family presence and participation were found to be helpful in reducing the patients' anxiety, improving communication (Coelho et al, 2022) and stabilising haemodynamic and respiratory indicators, such as blood pressure, pulse rate and respiratory rate (Lolaty et al, 2014); this was also found to be effective in reducing ventilator withdrawal time and complications due to positive pressure (Safaeepour et al, 2017). Haemodynamic and respiratory indicators such as blood pressure, pulse rate, respiratory rate, in the ICU are essential for preventing organ failure by ensuring stability between oxygen delivery and demand in the relevant tissues (Majumdar, 2017). Ultimately, when the ICU patient was with family, oxygen saturation improved, and the patient's oxygen demand decreased and PFCC is considered an important treatment guideline for ICUs to help patients and their families navigate the abovementioned challenges (Khaleghparast et al, 2016).…”
Section: Introductionmentioning
confidence: 99%